THE ROLE OF CYTOKINES IN SCHIZOPHRENIA - Binić, Iva; Petrović, Jovana; Antonijević, Jovana; Pančić, Dimitrije; Golubovic, Maša; Petrović, Filip; Branković, Jelena; Žikić, Olivera (Acta medicae Medianae, 2023)
Schizophrenia, a multisystem condition with an unclear cause, is linked to immunological dysfunctions, including altered cytokine levels. The possible role that inflammation could play in psychiatric diseases has been the subject of a growing corpus of research in the last 20 years. Individuals with schizophrenia have abnormal cytokine synthesis, abnormal cytokine concentrations, and altered cytokine receptors in their blood and cerebrospinal fluid, suggesting a relationship between inflammation and schizophrenia. Contradictory results have been observed in psychosis, leaving the pathophysiological function of inflammation in psychosis unclear. The population with chronic schizophrenia has been extensively investigated. Still, the group with first-episode psychosis (FEP) provides a unique chance to assess the biological, clinical, and functional consequences of psychotic illnesses. Results regarding cytokine concentration are inconsistent, which is a consequence of different research methodologies. However, it was found that there was a relationship between inflammation markers and disease symptoms. The development of biomarkers as quickly as possible following the onset of a disease might open the way for early disease prevention, which improves the prognosis. Intervention at an early stage stops the progression of the disease and enhances treatment outcomes. The drug-free FEP population is receiving a growing amount of attention from researchers who are conducting studies on a large scale.
Keywords: psychosis; inflammation; schizophrenia; biomarkers